Review on the Contracts Act 1950 : principles on communications / Jamaluddin Mohd Ali Jobran, Nur Athirah Md Jali and Sitizubaidah Zolkaply - Mohd Ali Jobran, Mohd Jamaluddin; Md Jali, Nur Athirah; Zolkaply, Siti Zubaidah (2013)
This project paper is concerned on the principles on communication under the law of contract. Basically, Section 3 and Section 4 of the Contracts Act 1950 provide the rules on communication. However, the provisions are too general. It is unclear whether the provision governs both the general contract transaction and the electronic transaction or it just governs the general contract transaction. Furthermore, adding to the confusion is the enactment of Electronic Commerce Act 2006 which governs online contracts. Even though the act is recent but it has been commented to be out dated. The scope of this project paper analyses the comprehensiveness of the laws dealing with communication of offer and acceptance, specifically Contracts Act 1950 and Electronic Commerce Act 2006. This project paper also compares the development that has taken place in other countries such as Singapore, Scotland and Australia. Lastly, recommendations are proposed to review and reform the current contract law principles on communication of offer and acceptance.